Analisis Resiko Pada UMKM XYZ Menggunakan Analisa Swot - Yuliatin Ali Syamsiah; Dwi Sukma Donoriyanto; Isna Nugraha (Student Scientific Creativity Journal, 2023)
This research aims to conduct risk analysis on Micro, Small and Medium Enterprises (MSMEs) with a case study on XYZ MSMEs using the SWOT analysis method. Risk analysis is crucial in identifying internal and external factors that can affect business continuity. By applying the SWOT approach, this research evaluates the strengths, weaknesses, opportunities and threats faced by XYZ MSMEs. By identifying these factors, this research provides a holistic picture of the internal and external conditions of XYZ MSMEs and the risks that may arise. The SWOT method is used as a tool to formulate an effective risk management strategy to increase the competitiveness and resilience of XYZ MSMEs in the market. The results of this analysis can be the basis for more targeted strategic decision making and risk planning in supporting the growth of MSMEs in a dynamic business environment.